2020
DOI: 10.1101/2020.08.10.20170894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the state of immune silence in fatal COVID-19 patients

Abstract: Since the beginning of the SARS-CoV-2 pandemic, COVID-19 has appeared as a unique disease with unconventional tissue and systemic immune features. While COVID-19 severe forms share clinical and laboratory aspects with various pathologies such as hemophagocytic lymphohistiocytosis, sepsis or cytokine release syndrome, their exact nature remains unknown. This is severely impeding the ability to treat patients facing severe stages of the disease. To this aim, we performed an in-depth, single-cell RNA-seq analysis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…We find evidence that ERG is central to a gene network linked to these cell populations, encoding a transcription factor important in determining lineage plasticity, modulating inflammation and maintaining an antithrombotic environment (Yuan et al, 2009). We further identify hallmarks supporting the importance of mononuclear phagocyte dysfunction in severe disease (Bost et al, 2021;Schulte-Schrepping et al, 2020), namely proliferating cMono, and specific monocyte populations showing reduced HLA-DR, CD33 and CD11c expression, high expression of antioxidant metallothionein and S100A8/9/12 (calprotectin), together with reduced pDCs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We find evidence that ERG is central to a gene network linked to these cell populations, encoding a transcription factor important in determining lineage plasticity, modulating inflammation and maintaining an antithrombotic environment (Yuan et al, 2009). We further identify hallmarks supporting the importance of mononuclear phagocyte dysfunction in severe disease (Bost et al, 2021;Schulte-Schrepping et al, 2020), namely proliferating cMono, and specific monocyte populations showing reduced HLA-DR, CD33 and CD11c expression, high expression of antioxidant metallothionein and S100A8/9/12 (calprotectin), together with reduced pDCs.…”
Section: Discussionmentioning
confidence: 74%
“…A dysregulated hyperinflammatory state occurs in some individuals (Moore and June, 2020), consistent with reported benefits from glucocorticoids (dexamethasone) and inhibitors of the IL-6 receptor (tocilizumab/sarilumab) and Janus kinases (baricitinib) in severe disease (Gordon et al, 2021;Horby et al, 2021a;Horby et al, 2021b;Kalil et al, 2021). Nevertheless, blood-derived signatures of COVID-19 severity are diverse, including evidence of immune suppression, myeloid dysfunction, lymphopenia, interferon driven immunopathology, T cell activation as well as exhaustion, and immune senescence (Bost et al, 2021;Chen and Wherry, 2020;Diao et al, 2020;Hadjadj et al, 2020;Mann et al, 2020;Schulte-Schrepping et al, 2020). In the lung, widespread neutrophil and macrophage infiltration, T cell cytokine production and alveolitis are seen with features of altered redox balance, endothelial damage and thrombosis (Grant et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…6A). This population has been identified in other COVID-19 datasets but is not yet well-characterized (21,63). These cells specifically and highly expressed genes encoding markers expressed at distinct stages in neutrophil development, including DEFA1B, LCN2, and MMP8 (Fig.…”
Section: Dynamic Changes In Nk Cell Receptors and Ligands May Underlimentioning
confidence: 83%
“…4J and suggests that the activated phenotype observed in these samples may be driven by activating signals received through DNAM-1 and NKG2D as well as a lack of inhibitory signaling through CD161. A hyperactivated neutrophil signature marks severe and fatal COVID-19 Despite evidence that neutrophils are major players in the dysregulated immune response defining severe and fatal COVID-19 (16,(18)(19)(20)(63)(64)(65)(66), there is a relative dearth of deep profiling of neutrophils from COVID-19 patients given their sensitivity to both cryopreservation and mechanical stimulation (67,68). To address this, we demonstrated that Seq-Well generated high-quality scRNA-seq data of primary human neutrophils from a healthy blood donor (Fig.…”
Section: Dynamic Changes In Nk Cell Receptors and Ligands May Underlimentioning
confidence: 99%
“…These results are similar to the previous reports describing the accumulation of MDSCs in patients with sepsis and septic shock [136][137][138] . In a recent preprint study, scRNA-seq was used to profile immune cells isolated from matched blood samples and broncho-alveolar lavage fluids of patients with COVID-19 and healthy controls 139 . This analysis revealed an immune signature of the disease severity that correlated with the accumulation of naive lymphoid cells in the lung and the expansion and activation of myeloid cells in peripheral blood.…”
Section: Other Emerging Roles For Mdscsmentioning
confidence: 99%